ANALISIS KANDUNGAN UNSUR HARA DAN TOTAL MIKROBA TANAH BEKAS PENAMBANGAN EMAS TANPA IZIN (PETI) DARI BEBERAPA KECAMATAN KABUPATEN KUANTAN SINGINGI - Sri Mulyani; Siti Zahrah; Sulhaswardi Sulhaswardi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This unlicensed gold mining activity (PETI) can have a positive impact on the economy of the community, in the form of increased incomes so that it can improve the welfare of the community. However, besides having a positive impact, PETI's activities will harm the environment around the mining area. The negative impact caused by mining activities is environmental damage in the form of a decrease in land quality as indicated by a decrease in physical, chemical and biological soil quality. The purpose of this study was to determine the nutrient content and the total of microbes in former PETI soils in sub-districts of the Kuantan Singingi Regency. The parameters observed were analysis of nutrient content consisting of analysis of sand, dust, clay, soil pH, C-organic, N-total, P2O5, K2O, interchangeable cations, CEC, a saturation of bases, Aluminum Saturation, and analysis of total soil microbes. The results showed that the Singingi sub-district, Central Kuantan sub-district, Sentoja sub-district, and Logas Tanah Darat sub-district has the texture of sand soil clay to sand, the content of pH H2O Land classified as fertility is very sour, C-Organic (%), Ca-dd, Nitrogen-Total (%), Mg-dd and CEC with very low fertility criteria, C/N Ratio with low to very low fertility criteria, K-dd content with low criteria, Na-dd with moderate to very high criteria, aluminum saturation is very high with wet saturation the fertility criteria are low. The total microbes in the Sub-district of Sentoja Raya and Logas Tanah Darat Sub-district are much higher than Singingi Sub-district and Central Kuantan Sub-district.